DIDACTIC ASPECTS OF LITERARY TEXT STUDYING WITHIN ELEMENTARY SCHOOL CLASSES - Silvia GOLUBIŢCHI (Acta et Commentationes, Sciences of Education, 2019)
Text study emphasizes literary code deciphering. There are various types of literary texts, eachwith a variety of approaches to be explored within classes. Each class begins with a preparatory activityin the text world, followed by text reading that stipulates the next conditions: reading condition as event,lecturer's condition as performance, condition of poetic text as a work, condition of interpretation as anact of comprehension and recreation. Any text deciphering has at its basis two operations: comprehensionand interpretation.